Lactobacillus acidophilus and HKL Suspension Alleviates Ulcerative Colitis in Rats by Regulating Gut Microbiota, Suppressing TLR9, and Promoting Metabolism - Aximujiang, Kasimujiang; Kaheman, Kuerbannaimu; Wushouer, Xilinguli; Wu, Guixia; Ahemaiti, Abulaiti; Yunusi, Kurexi (Frontiers in Pharmacology, 2022)
Ulcerative colitis(UC) is a chronic nonspecific inflammatory bowel disease with complex pathogenesis.The disturbance of intestinal flora affects the homeostasis of the intestinal environment, leading to metabolic imbalance and immune abnormalities of the host,contributes to the perpetuation of intestinal inflammatory processes. We Postulate that the combination of anti-inflammatory therapy and the regulation of intestinal flora balance may be more helpful for the treatment of UC. The research team used Lactobacillus acidophilus (Lac) and Chinese medicine HKL suspension (HKL) to interfere with UC rats , and the combined intervention(LH) effect was better than the single intervention group, but its mechanism is not clear. In this study, employed 16S rRNA sequencing, Immunohistochemical, ELISA methods in colon samples and untargeted metabolomics profiling in serum samples investigating its underlying mechanism. Results indicated that LH treatment significantly up-regulated the protein expression levels of L-13, TGF-β and down-regulated TLR9 and TLR4 in the colon tissue of UC rats, which had obvious anti-inflammatory effect. LH treatment could shape the gut microbiota structure and modify metabolic profiles. The abundance of opportunistic pathogens such as Klebsiella and Escherichia-Shigella correlated with intestinal inflammation markedly decreased, while the levels of beneficial bacteria including Bifidobacterium , Romboutsia, lactobacillus,Ruminococcaceae_UCG-014, Ruminococcaceae_UCG-010 and Lachnospiraceae _NK4B4_ group. elevated in various degrees. Bifidobacterium was significantly enriched in LH group and positively correlated with IL-13 and TGF-β, while negatively correlated with IFN-γ. The energy metabolism, amino acid metabolism and lipid metabolism were disturbed in UC group. LH treatment can alleviate the state of energy deficiency in colonic epithelium of rats in UC group by promoting the increase of short-chain fatty acid (SCFA)producing bacteria such as Ruminococcaceae_UCG_ 014, Ruminococcaceae_ UCG_010, Romboutsia, norank-f-Coriobacteriaceae. LH treatment affected the metabolism of lactic acid, creatine and glycine by inhibiting the growth of Klebsiella. In all, our results suggested that the combination of Lactobacillus acidophilus and HKL suspension might exert a beneficial role in UC by modulating gut microbiota signature with correlated metabolites, TLR9 and cytokines in different pathways.The combined intervention of probiotics and Traditional Chinese medicine is a novel method in the treatment of UC.